Rekonstruksi Penetapan Masa Haid dalam Perspektif Empat Mazhab - Najib, M. Ainun; Musyafa'ah, NurLailatul; Syafaq, Hammis (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2024)
This article explores the determination of menstruation duration from the perspectives of the four major Sunni schools of Islamic jurisprudence: Hanafi, Maliki, Shafi’i, and Hanbali. The primary focus is on the differences in the minimum and maximum durations of menstruation, as well as the underlying reasons for these variances. The study examines the methodological foundations of each school in determining the menstrual cycle. This research employs a normative legal approach with a conceptual framework. Primary sources are in the form of books from the four schools, and secondary sources include books, research, and scientific articles related to menstrual fiqh. Data collection is conducted through literary data tracing, which is then analyzed descriptively. The findings highlight that the diversity of opinions stems from epistemological and methodological distinctions in interpreting scriptural texts and responding to the lack of authentic hadiths regarding the duration of menstruation. This research provides a comprehensive understanding of the richness of Islamic jurisprudence, emphasizing that legal pluralism is a manifestation of intellectual diversity and divine mercy in Islam.